2017
DOI: 10.1016/j.leukres.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and mechanisms contributing to TKI-induced vascular events in patients with CML

Abstract: Vascular adverse events (VAE) are an emerging problem in patients with chronic myeloid leukemia (CML) receiving second-generation BCR-ABL1 tyrosine kinase inhibitors (TKI). Relevant VAE comprise peripheral, cerebral, and coronary artery changes in patients receiving nilotinib, venous and arterial occlusive events during ponatinib therapy, and pulmonary hypertension in patients receiving dasatinib. Although each TKI binds to a unique profile of molecular targets in leukemic cells and vascular cells, the exact e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 97 publications
0
45
0
3
Order By: Relevance
“…AOEs represent off‐target relevant complications of TKIs, particularly second‐generation and third‐generation TKIs . Nilotinib and ponatinib interact with a considerable number of clinically relevant vascular targets implicated in endothelial cell survival and angiogenesis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AOEs represent off‐target relevant complications of TKIs, particularly second‐generation and third‐generation TKIs . Nilotinib and ponatinib interact with a considerable number of clinically relevant vascular targets implicated in endothelial cell survival and angiogenesis …”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular profile of 85 patients and management of 26 cardiovascular adverse events Based on sex, age, smoking, systolic pressure, and cholesterol level.AOEs represent off-target relevant complications of TKIs, particularly second-generation and third-generation TKIs. 14 Nilotinib and ponatinib interact with a considerable number of clinically relevant vascular targets implicated in endothelial cell survival and angiogenesis 15. …”
mentioning
confidence: 99%
“…9 Strategies to predict the overall likelihood of VAEs have been proposed 1,17,18 and have formed the basis of recommendations for pre-TKI risk assessment and the avoidance of nilotinib where possible in those at higher risk. 2,9 In addition, regular monitoring for risk factors throughout treatment is recommended, with some authors suggesting a role for angiologic testing such as ankle-brachial index assessment 2,19 and computed tomography coronary calcium scores. 9 In line with previous findings, we demonstrated that VAEs were more common in older patients 20 and in those with preexisting cardiovascular risk factors.…”
Section: Months After First Vaementioning
confidence: 99%
“…6,7 The incidence of nilotinib-associated VAEs ranges from 0.5% to 35% of patients in published literature. 2,[8][9][10][11] Factors contributing to the variability include inconsistent duration of follow-up, lack of a standardized definition of vascular events, 8 and exclusion of patients with a history of impaired cardiac function in some randomized controlled trials. 3,10 Despite the increasing understanding of the incidence and predisposing risk factors for nilotinib-associated AEs, there is a paucity of data to assist clinicians in their management.…”
Section: Introductionmentioning
confidence: 99%
“…As vascular events can occur years after initiating therapy, long-term follow-up of many CML patients is necessary to distinguish the background risk in this older population (average age, 64 years) from the enhanced risk induced directly by the TKI. 4 Bosutinib was recently approved for first-line treatment of CML, although sufficient long-term vascular safety data are not yet available. A meta-analysis of BCR-ABL TKI trials confirmed the significant increased vascular risk with dasatinib, nilotinib, and ponatinib, but the bosutinib data were limited by insufficient power.…”
Section: Introductionmentioning
confidence: 99%